Moving Pictures, Moving Forward: the Future of Enjoying Cinema - Jang, Yunseo; Kang, Jiho (Eximia, 2025)
The advancement of technology and platforms is fundamentally reshaping cinema. How we consume movies has changed drastically: people have progressed from watching movies at theaters to using phones. There is a threat to the old form of cinema, which is the growing number of streaming services. Alternative platforms such as VR, interactive story-based games, and specialized theaters like Superplex are forcing filmmakers to adapt to these new shifts. Are movies evolving? Do these changes in technology directly influence filmmaking techniques, such as the use of framing, editing, and narrative structures? We define evolution as the gradual development of something into a more complex form, and we hope to prove that movies are indeed evolving. Rather than simply reacting to new platforms, cinema is transforming and adapting its storytelling, visuals, and formats to fit the changing ways audiences consume and experience film.